Analisa Jaringan 4G LTE Provider H3I Menggunakan Software Genex Probe 5.1 - Muliandhi, Puri; Jayati, Ari Endang; Hidayati, Latifah (Elektrika, 2023)
Telecommunication technology is currently developing so fast, along with the need for people to communicate. 4G LTE network technology has many positive impacts on service users in communication access. Every provider user wants to have good network quality when used in exchanging information and communications. This study discusses the analysis of the quality of the 4G LTE network in the Purwokerto area by taking a drive test data. Analysis of the drive test is carried out using Map Info software to determine the signal condition in accordance with the range provider and the calculation of the percentage each month with 4G parameters, namely RSRP (Reference Signal Received Power) and SINR (Signal to Interference Noise Ratio). The result of this analysis is a comparison of network quality in December 2019 based on the RSRP and SINR parameter values. In December, the RSRP value that met the standard ≥ = -95 dBm reached a percentage of 77.23% and in March it reached a percentage of 81.86%. For the SINR value in December 2019 which met the standard ≥ = 12 dB, it reached a percentage of 36.82% and in March it reached a percentage of 46.08%. Keywords: Network Analysis, LTE, Genex Probe, RSRP, SINR  ABSTRAK  Teknologi telekomunikasi saat ini berkembang begitu cepat, seiring dengan kebutuhan orang dalam berkomunikasi. Teknologi jaringan 4G LTE memberikan banyak dampak positif bagi pengguna layanan dalam akses komunikasi. Setiap pengguna provider pasti berkeinginan untuk memiliki kualitas jaringan yang baik saat digunakan dalam bertukar informasi dan komunikasi. Penelitian ini membahas tentang Analisa kualitas jaringan 4G LTE di daerah Purwokerto dengan pengambilan data drive test. Analisa drive test dilakukan menggunakan software Map Info untuk mengetahui kondisi sinyal yang sesuai dengan range provider dan perhitungan persentase setiap bulannya dengan parameter 4G yaitu RSRP (Reference Signal Received Power) dan SINR (Signal to Interference Noise Ratio). Hasil dari analisa ini adalah perbandingan kualitas jaringan pada bulan Desember 2019 berdasarkan nilai parameter RSRP dan SINR. Untuk bulan Desember nilai RSRP yang memenuhi standar ≥=-95 dBm mencapai persentase 77.23% dan bulan Maret mencapai persentase 81.86%. Untuk nilai SINR bulan Desember 2019 yang memenuhi standar ≥=12 dB mencapai persentase 36.82% dan bulan Maret mencapai persentase 46.08%.